2014
DOI: 10.1016/j.jval.2014.08.2501
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Fidaxomicin for the Treatment of Clostridium Difficile Infections (CDI) also Known as Clostridium Difficile-Associated Diarrhoea (CDAD) in Spain

Abstract: comycin in the treatment of adult CDI patients. The analysis focused on three CDI patient subgroups: cancer, concomitant antimicrobials, and renal impaired patients. Methods: A Markov model was developed with a cycle length of 10 days and a one year time horizon. The patient enters the model in the CDI health state and is treated with fidaxomicin, or vancomycin for 10 days. Health state utilities were derived from the literature. The model perspective was the Spanish health care provider. Deterministic and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Of the 13 EEs reported as full publications, six [ 26 , 27 , 46 , 58 , 62 , 65 ] had previously been presented at a conference [ 38 , 41 , 45 , 52 , 63 , 66 ] and posters were sourced for all except one [ 45 ]. For the remaining EEs, the data were reported in abstract ( n = 7) [ 36 , 39 , 49 , 53 , 54 , 56 , 57 , 59 ] or poster form ( n = 7) only [ 40 , 43 , 44 , 47 , 51 , 60 , 61 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 EEs reported as full publications, six [ 26 , 27 , 46 , 58 , 62 , 65 ] had previously been presented at a conference [ 38 , 41 , 45 , 52 , 63 , 66 ] and posters were sourced for all except one [ 45 ]. For the remaining EEs, the data were reported in abstract ( n = 7) [ 36 , 39 , 49 , 53 , 54 , 56 , 57 , 59 ] or poster form ( n = 7) only [ 40 , 43 , 44 , 47 , 51 , 60 , 61 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies had compared the recurrence rate and average hospital stay of CDI patients treated with 2 antibiotics, which showed that the cost-effectiveness of fidaxomicin in the treatment of CDI was more advantageous than that of vancomycin. [25][26][27] However, drug prices and hospitalization costs vary greatly in different regions, and the cost-effectiveness of drugs should be determined according to local conditions.…”
Section: The Cost-effectiveness Of Fidaxomicin Versus Vancomycin In T...mentioning
confidence: 99%